Characteristics of infertile couples in Santiago de Cuba - Guillermo Mora García (Medisan, 2019)
Introduction: The incidence of infertility has increased and, according to expert doctors and diverse specialized organizations, a clear relationship exists between the system of current life and the decrease of fertility.